47.1k views
4 votes
Express the function as the sum of a power series by first using partial fractions. f(x)=x+62x2−9x−5

User Xbalaji
by
5.5k points

1 Answer

2 votes

Answer:


(x+6)/(2x^2-9x+5)=-\sum_(n=0)^(\infty) [(-2)^(n)x^(n) + (x^(n))/(5^(n+1))]

when:


|x|<(1)/(2)

Explanation:

In order to solve this problem, we must begin by splitting the function into its partial fractions, so we must first factor the denominator.


(x+6)/(2x^2-9x+5)=(x+6)/((2x+1)(x-5))

Next, we can build our partial fractions, like this:


(x+6)/((2x+1)(x-5))=(A)/(2x+1)+(B)/(x-5)

we can then add the two fraction on the right to get:


(x+6)/((2x+1)(x-5))=(A(x-5)+B(2x+1))/((2x+1)(x-5))

Since we need this equation to be equivalent, we can get rid of the denominators and set the numerators equal to each other, so we get:


x+6=A(x-5)+B(2x+1)

and expand:


x+6=Ax-5A+2Bx+B

we can now group the terms so we get:


x+6=Ax+2Bx-5A+B


x+6=(Ax+2Bx)+(-5A+B)

and factor:


x+6=(A+2B)x+(-5A+B)

so we can now build a system of equations:

A+2B=1

-5A+B=6

and solve simultaneously, this one can be solved by substitution, so we get>

A=1-2B

-5(1-2B)+B=6

-5+10B+B=6

11B=11

B=1

A=1-2(1)

A=-1

So we can use these values to build our partial fractions:


(x+6)/((2x+1)(x-5))=(A)/(2x+1)+(B)/(x-5)


(x+6)/((2x+1)(x-5))=-(1)/(2x+1)+(1)/(x-5)

and we can now use the partial fractions to build our series. Let's start with the first fraction:


-(1)/(2x+1)

We can rewrite this fraction as:


-(1)/(1-(-2x))

We can now use the following rule to build our power fraction:


\sum_(n=0)^(\infty) ar^(n) = (a)/(1-r)

when |r|<1

in this case a=1 and r=-2x so:


-(1)/(1-(-2x))=-\sum_(n=0)^(\infty) (-2x)^n

or


-(1)/(1-(-2x))=-\sum_(n=0)^(\infty) (-2)^(n) x^(n)

for: |-2x|<1

or:
|x|<(1)/(2)

Next, we can work with the second fraction:


(1)/(x-5)

On which we can factor a -5 out so we get:


-(1)/(5(1-(x)/(5)))

In this case: a=-1/5 and r=x/5

so our series will look like this:


-(1)/(5(1-(x)/(5)))=-(1)/(5)\sum_(n=0)^(\infty) ((x)/(5))^n

Which can be simplified to:


-(1)/(5(1-(x)/(5)))=-\sum_(n=0)^(\infty) (x^n)/(5^(n+1))

when:


|(x)/(5)|<1

or

|x|<5

So we can now put all the series together to get:


(x+6)/(2x^2-9x+5)=-\sum_(n=0)^(\infty) [(-2)^(n)x^(n) + (x^(n))/(5^(n+1))}

when:


|x|<(1)/(2)

We use the smallest interval of convergence for x since that's the one the whole series will be defined for.

User Manik Biradar
by
4.4k points